Radiation Therapy in Adult Soft Tissue Sarcoma—Current Knowledge and Future Directions: A Review and Expert Opinion - Roeder, Falk (Cancers (Basel), 2020)
SIMPLE SUMMARY: Radiation therapy (RT) is an integral part of the treatment of adult soft-tissue sarcomas (STS). Although mainly used as perioperative therapy to increase local control in resectable STS with high risk features, it also plays an increasing role in the treatment of non-resectable primary tumors, oligometastatic situations, or for palliation. This review summarizes the current evidence for RT in adult STS including typical indications, outcomes, side effects, dose and fractionation regimens, and target volume definitions based on tumor localization and risk factors. It covers the different overall treatment approaches including RT either as part of a multimodal treatment strategy or as a sole treatment and is accompanied by a summary on ongoing clinical research pointing at future directions of RT in STS. ABSTRACT: Radiation therapy (RT) is an integral part of the treatment of adult soft-tissue sarcomas (STS). Although mainly used as perioperative therapy to increase local control in resectable STS with high risk features, it also plays an increasing role in the treatment of non-resectable primary tumors, oligometastatic situations, or for palliation. Modern radiation techniques, like intensity-modulated, image-guided, or stereotactic body RT, as well as special applications like intraoperative RT, brachytherapy, or particle therapy, have widened the therapeutic window allowing either dose escalation with improved efficacy or reduction of side effects with improved functional outcome. This review summarizes the current evidence for RT in adult STS including typical indications, outcomes, side effects, dose and fractionation regimens, and target volume definitions based on tumor localization and risk factors. It covers the different overall treatment approaches including RT either as part of a multimodal treatment strategy or as a sole treatment, namely its use as an adjunct to surgery in resectable STS (perioperative RT), as a primary treatment in non-resectable tumors (definitive RT), as a local treatment modality in oligometastatic disease or as palliative therapy. Due to the known differences in clinical course, general treatment options and, consequently, outcome depending on lesion localization, the main part of perioperative RT is divided into three sections according to body site (extremity/trunk wall, retroperitoneal, and head and neck STS) including the discussion of special applications of radiation techniques specifically amenable to this region. The review of the current evidence is accompanied by a summary on ongoing clinical research pointing at future directions of RT in STS.